PENGARUH SALURAN DISTRIBUSI DAN PROMOSI TERHADAP KINERJA PEMASARAN (STUDI KASUS PADA UKM FURNITURE KOTA SEMARANG) - Sendhang Nurseto (Universitas Diponegoro, 2017)
Every year the realization of expected production is not in accordance with the desired target. Realization of production every year on average only reaches 90 % of the target. The resulting production also fluctuated every year, almost every year has decreased. These results are certainly not as expected, where craftsmen certainly want to increase production annually. Another phenomenon that shows the weakness of the development of furniture SMEs in Semarang. It was also supported by previous studies that include : a) Lack of distribution channels used , b) Lack of promotional activities that have been performed. The problems in this research are ; a) How does the Infuence of Distribution Channels to Marketing Performance?, b) How does the Infuence of Promotion to Marketing Performance?, c) How does the Infuence of Distribution Channels and Promotion to Marketing Performance simultaneously? Results from this study are, there is an influences of distribution channels for marketing performance , with 5,751 t value and significance 0.000 < 0.005 . There is an influenceof promotion on the performance of the marketing campaign with 8,631 t value and significance 0.000 <0.005 . There is the influence of distribution channels and promotion simultaneously on marketing performance with F count 38.788 and significance 0.000 <0.005 . Suggestions can be submitted by the authorare ; Until now, SMEs Furniture Semarang have enough distributors. There are even some who are able to distribute their products to outside the city .However , according to the researchers there are some things that could be improved . Among other things need to improve is the convenience for the customer visiting the store . Promotion is done by entrepreneurs pretty good , among others, the most Infuenceive is through word of mouth . But it would be better if employers follow the exhibition events held in major cities on a regular basis.